Clinical Decision-Making And Risk Management In Nursing, Family Medicine, Anesthesia, And Public Health Settings (The Review of Diabetic Studies, 2024)
Introduction: Clinical decision-making and risk management are critical for ensuring patient safety and quality care across nursing, family medicine, anesthesia, and public health. Healthcare professionals face complex decisions under uncertainty, time pressure, and rapidly evolving clinical and technological environments.Aim of Work: This study aims to examine how healthcare professionals manage uncertainty, integrate technological tools, and address ethical and organizational factors that influence patient outcomes and healthcare quality.Methods: A descriptive–analytical approach was used based on a structured review of recent literature from 2020 to 2024, including observational studies, qualitative research, and systematic reviews focusing on clinical reasoning, risk assessment, informatics, and precision medicine.Findings: Uncertainty is a pervasive challenge in clinical decision-making, particularly in high-risk settings such as anesthesia and emergency care. Structured clinical reasoning, interprofessional collaboration, and health informatics improve risk management and patient outcomes. However, challenges persist related to data quality, algorithmic bias, equity, and professional well-being, highlighting the need for ethical and organizational support.Conclusion: Effective decision-making and risk management require an integrated approach combining technology, ethical principles, professional judgment, and supportive healthcare systems to enhance patient safety and overall quality of care.